2013
DOI: 10.1111/mmi.12460
|View full text |Cite
|
Sign up to set email alerts
|

A Francisella virulence factor catalyses an essential reaction of biotin synthesis

Abstract: Summary We recently identified a gene (FTN_0818) required for Francisella virulence that seemed likely involved in biotin metabolism. However, the molecular function of this virulence determinant was unclear. Here we show that this protein named BioJ is the enzyme of the biotin biosynthesis pathway that determines the chain length of the biotin valeryl side chain. Expression of bioJ allows growth of an E. coli bioH strain on biotin-free medium, indicating functional equivalence of BioJ to the paradigm pimeloyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(121 citation statements)
references
References 55 publications
(124 reference statements)
12
109
0
Order By: Relevance
“…2c). Note that despite its low sequence identity with E. coli BioH the P. aeruginosa protein is clearly a BioH and not one of the other pimeloyl-ACP methyl ester esterases because those nonorthologous proteins cannot be aligned with E. coli BioH even given very permissive alignment parameters 24, 25, 30 .
Figure 2Sequence alignments, purification and modeling of BioH proteins. (A), sequence alignment of the BioH proteins of E. coli and P. aeruginosa PAO1.
…”
Section: Resultsmentioning
confidence: 99%
“…2c). Note that despite its low sequence identity with E. coli BioH the P. aeruginosa protein is clearly a BioH and not one of the other pimeloyl-ACP methyl ester esterases because those nonorthologous proteins cannot be aligned with E. coli BioH even given very permissive alignment parameters 24, 25, 30 .
Figure 2Sequence alignments, purification and modeling of BioH proteins. (A), sequence alignment of the BioH proteins of E. coli and P. aeruginosa PAO1.
…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the recombinant plasmid pBAD24:: lptA was constructed through cloning of the Neisseria LptA-encoding gene into pBAD24 (S1 Table). Using the pBAD24:: mcr - 1 plasmid as the template, The experiments of site-directed PCR mutagenesis were conducted as we earlier described [47]. All the acquired plasmids were verified by PCR assays and direct DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic studies have revealed important roles for biotin biosynthesis in Mycobacterium tuberculosis during growth, infection and the latency phase, thus establishing this pathway as a potential drug target for new anti-tuberculosis therapies [3], [8], [9], [10], [11] and [12]. In addition, biotin biosynthesis has been intensively studied in other bacteria and the enzymes involved in the pathway have been implicated in bacterial virulence during infection and intracellular replication [13].…”
Section: Introductionmentioning
confidence: 99%